The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1039/c9rp00014c
|View full text |Cite
|
Sign up to set email alerts
|

South African university students’ attitudes towards chemistry learning in a virtually simulated learning environment

Abstract: This mixed method study investigated changes in 3rd year Bachelor of Education students’ attitudes towards chemistry after learning interventions with virtual chemistry simulations. After participant students identified certain concepts from their 3rd year chemistry module as being abstract and not easily comprehensible, these concepts were facilitated during a 5 week learning intervention using PhET simulations as an alternative to traditional laboratory experimentation. In the first quantitative phase of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 33 publications
1
41
0
Order By: Relevance
“…Furthermore, research has shown that PhET interactive simulations have been reported to students' learning performance (Debowska et al, 2013) and PhET simulations have been reported to improve students' conceptual understanding (Clark and Chamberlain, 2014). Additionally, researchers report that PhET simulations provided students with experience that is joyful and autonomous, promoted a positive attitude towards chemistry, and nurtured their ability to visualize concepts in chemistry which results in improving conceptual understanding (Penn & Ramnarain, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, research has shown that PhET interactive simulations have been reported to students' learning performance (Debowska et al, 2013) and PhET simulations have been reported to improve students' conceptual understanding (Clark and Chamberlain, 2014). Additionally, researchers report that PhET simulations provided students with experience that is joyful and autonomous, promoted a positive attitude towards chemistry, and nurtured their ability to visualize concepts in chemistry which results in improving conceptual understanding (Penn & Ramnarain, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Similar to the findings of this current study, Stafford et al (2010), noted that students found virtual experimentation rather costeffective. Several other studies across different science subjects (Chua & Karpudewan, 2017;Estapa, & Nadolny, 2015;Hsu, et al, 2017;Merchant et al, 2014;Penn & Ramnarain, 2019) found that virtual experimentation was positively beneficial for enhancing attitudes, motivation, procedural and conceptual understandings of science concepts across subjects. In principle the findings of this study also show that while social distancing and maintaining the recent COVID-19 pandemic regulations, students can still experiment online and collaborate with their peers while doing so (Vasiliadou, 2020).…”
Section: Discussionmentioning
confidence: 97%
“…The infusion of technology in 21 st century science learning, has provided applications whereby active learning can be done in virtual science laboratories. These virtually based science laboratories have enhanced science teaching and learning and played a significant role in learners' understandings of, visualization and engagement with abstract scientific concepts (Estapa & Nadolny, 2015;Penn & Ramnarain, 2019). In addition to the work of Piaget and Dewey, social constructivists advocate that learning is a social process (Vygotsky, 1978) and learning activities should be considerate of the learners' context and daily experiences (Mavuru & Ramnarain, 2017).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…11 However, it is acknowledged that despite their benefits, computergenerated simulations and online resources alone cannot replicate the practice and authentic experience of a real laboratory class but rather complement them. 12 The shift in attitude towards laboratory instruction is also reflected in recent articles about laboratory assessment. This requires a close look at learning outcomes and skills matrices relevant to practical instruction 13,14 and formulating desired key competencies 15 .…”
Section: State Of Affairsmentioning
confidence: 99%